Residencia universitaria con servicios complementarios en el Centro Histórico de Lima - Contreras Romero, Rodrigo Raul (2024)
One of the most influential factors in the progress of individuals and societies is education. Higher education is the key to the development of the country. In Peru, many young people from different regions are forced to move to the capital, as 40% of universities are located in Lima alone. However, only 2 of the 57 universities have university residences, which is insufficient to meet the high demand for student accommodation. This situation is particularly difficult for students who already face the challenge of living away from their families and who do not have sufficient resources to find affordable accommodation, increasing their chances of dropping out. In light of the above, NODOS was born. It is a university residence project in the Historic Center of Lima that aims to fill this gap by providing students with an appropriate environment and the necessary resources. NODOS not only offers accommodation, but also complementary spaces that support the academic and social development of students. Despite its great historical and tourist importance, the Historic Center of Lima has suffered from deterioration, unsafety and a loss of attractiveness. The revitalization of this area is of paramount importance. Therefore, this project aims to improve the current conditions and promote heritage conservation. NODOS seeks to establish itself as an urban hub, merging academic and social services for the benefit of both students and the local community. Educational and urban development will benefit from the proximity of several universities and improved infrastructure. This approach will not only meet the needs of the students but also contribute to the revitalization of the Historic Center of Lima, thereby improving the quality of life and enhancing the attractiveness of this emblematic area of the city. The project is expected to serve as a replicable model for other parts of the city.